Demographic studies on various cardiac diseases in dogs - K. Rajkumar; C. Ansar Kamran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The occurrences of various cardiac disorders on prospective study of 82 cases were studied. Dilated Cardiomyopathy was recorded in 37(45.1%) cases followed by Mitral Valve Disease in 26(31.7%), Hypertrophic Cardiomyopathy in 6(7.3%), Patent Ductus Arteriosus in 8(9.8%), Aortic Stenosis in 2(2.4%) and Atrial Septal defect in 2(2.4%) cases. Cardiac disease was found to be highest in Labrador Retriever (27.2%), followed by German Shepherd (15.2%). The occurrence of cardiac disease was 15.9 per cent in pups up to one year followed by 17 per cent in 1 to 3 years old dogs, 23 per cent in 3 to 6 years, 19 per cent in 6 to 9 years and 10 per cent above 9 years of age. With respect to gender, the occurrence of cardiac disease was more in males (68.5 %) than in females (31.5%).